Conflict Management Styles and Staff’ Job Satisfaction at Organization - Aida Mehrad (Universitas Ahmad Dahlan, 2015)
Abstract One of the important organizational factors among staffs is job satisfaction. This inner feeling assumed as basic factor that emerged by various elements at workplace. According to the different role of elements that effect on job satisfaction, organization’s managers should be consider the correct styles of management. In reality, lack of consideration to this human need leads to appear various abnormal behaviors at organization. The main purpose of present literature review is focused on the vital role of conflict management styles on job satisfaction among staff and also examines relationships between conflict management styles and job satisfaction at workplace. In reality, momentous regard should be dedicated the accurate management styles at organization. Correspondingly, the precise management styles as external element have noticeable role on job satisfaction at organization because each of these styles can advance the obligation of staff toward organization. The current initiative is about improving job satisfaction among staff and finding exact management style which is one of the central parts of organization progress. Keyword: Conflict Management Styles, Job Satisfaction, Staff, Organization